Gastric Histopathology of Chronic Gastritis in Obese Patients Undergoing Laparoscopic Sleeve Gastrectomy: A Local Experience - Murad A. Alturkustani (Journal of King Abdulaziz University: Medical Sciences, 2023)
A retrospective review was conducted using the database at King Abdulaziz University Hospital, to determine the most common cause of chronic gastritis among obese individuals. One hundred and thirty-one specimens were examined, obtained from patients who had laparoscopic sleeve gastrectomy and diagnosed with chronic gastritis. Helicobacter pylori was detected in 15 cases only. The most common diagnosis was “Chronic inactive gastritis without Helicobacter pylori infection” in 57 (43.50%) cases, then “Chronic gastritis with lymphoid follicular hyperplasia” in 54 (41.20%) cases, and lastly “Chronic active gastritis” in the remaining 20 (15.20%) Cases. The low incidence of Helicobacter pylori infection even in cases of gastritis with lymphoid follicular hyperplasia support the existence of the new proposed entity (i.e., obesity-related gastritis). Biopsy specimens for cases diagnosed as chronic gastritis were used as control group to confirm the appropriate rate of detecting Helicobacter pylori organisms by morphological examination in the same laboratory. In these biopsies, Helicobacter pylori was present in (50.70%), and reactive follicular hyperplasia was detected in (6%) of total controls.